Fintech and access to finance - Bollaert, Helen; Lopez-de-Silanes, Florencio; Schwienbacher, Armin (Journal of Corporate Finance, 2021)
This article surveys research on the effects of digitalization on access to finance. We focus the review on access through fintech. We review the growth of three main fintech technologies, fintech lending (incl. peer-to-peer lending), crowdfunding and initial coin offerings. We discuss existing evidence on how fintech affects access to finance for firms and investors and consider the regulatory challenges it poses. We incorporate the papers in this special issue, underlining their significant contributions to our understanding of the digitalization of finance and its effects. Finally, we discuss the challenges of research in the digital finance area and propose some new avenues for future research.